ANALISIS HAK PENCABUTAN KEMBALI ATAS HIBAH YANG TELAH DIBERIKAN ORANGTUA KEPADA ANAK DALAM HUKUM ISLAM (KAJIANATAS PUTUSAN MAHKAMAH AGUNG NOMOR : 78K/AG/ 2012) - ,, Nurul Bisyarati; ,, Agus Rianto (PARENTAL, 2014)
ABSTRACT This research aimed to find out how the law of gift withdrawal was according to Islamic heir law and the judgeâs rationale in deciding the Supeme Courtâs verdict Number 78K/AG/2012 about gift (hibah). This study was a normative law research that was prescriptive and applied in nature, using case approazh to the case of right ti withdraw the gift that has been given by the parents to child in Islamic Law. This study employed primary and secondary law materials. The technique of collecting law material employed was library study. The law material analysis was conducted using deductive method by explaining general item and then the particularly one, so that finally a conclusion could be drawn. In this study, the major premise was Islamic rule of law (Islamic Law Compilation), while the minor one was the Supreme Courtâs verdict Number 78K/AG/2012. From the two premises, a conclusion could be drawn. Considering the result of research and discussion, it could be concluded that the law of gift withdrawal according to Islamic heir law was not been allowed expect for the gift from parents to their child. The article 212 of Islamic Law Compilasion mentioned that the parentâs gift to child could be withdrawn. The appealer could not show the judex factie guilt in applying the law. Thus, the Supreme Courtâs deliberation could be justified, because the Judge had legal rationale or ratio decidendi that was juridical and non juridical in nature, that met the provisions of Law. Keywords : Withdrawal Righgt, Gift (Hibah), Islamic Law.